Faktor Sosial Ekonomi yang Mempengaruhi Minat Penggunanna Mobile Bangking BRIMO: (Studi Kasus: Nasabah PT Bank Rakyat Indonesia Kantor Cabang Watampone) (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the effect of socio-economic factors on interest in using the BRImo mobile banking application among customers of PT Bank Rakyat Indonesia Watampone Branch Office. The factors analyzed include education level, income, occupation, perceived convenience, and perceived security. This research uses a quantitative approach with a survey method of 100 respondents selected through simple random sampling technique. Data were analyzed using binary logistic regression. The results showed that only perceived ease of use had a significant effect on interest in using BRImo, while education, income, employment, and perceived security had no significant effect. These findings indicate the importance of ease of use as a major factor in driving the adoption of digital banking services.